Correspondence upon the conveyance to the crown of certain lands by the Hudson's Bay Company [electronic resource]. - Douglas, James, Sir, 1803-1877.; Vancouver Island (B.C.). Governor (1851-1863 : Douglas) (Victoria, B.C. : [s.n.], 1863)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 17274-17277. At head of p. [1] : Part III. Electronic reproduction. Mode of access: Internet. 44